STEM Learning: the Key to Developing Critical Thinking Skills in Students - Ekayanti, Ni Wayan; Hermawan, I Made Surya; Arjaya, Ida Bagus Ari (Universitas Pendidikan Ganesha, 2025)
There is an urgent need to improve and strengthen critical thinking skills among students. This study aims to analyze STEM learning: the key to developing critical thinking in students. This secondary study uses the Systematic Literature Review (SLR) method. Data were collected using the Prisma model from 2014 to 2024, in the form of published articles on STEM and critical thinking indexed by Sinta (1 and 2) and/or Scopus. The data were analyzed qualitatively, showing that STEM research on critical thinking began to receive academic attention in 2018, with a peak of publications in 2023. Since 2018, publications in reputable journals such as Scopus and SINTA have experienced a surge, especially in the SINTA 2 and Scopus Q2/Q4 categories. STEM is most widely applied at the high school and tertiary levels, showing that 83.33% of students experienced an increase in critical thinking after implementing STEM, with the highest effectiveness in the Project-Based Learning (PjBL) model. The implications of this research confirm that STEM education plays a significant role in improving critical thinking skills, and predictions of future research trends will focus on exploring more specific and innovative approaches to optimizing STEM implementation in education.